Alternating Direction Method for a Class of Sylvester Matrix Equations with Linear Matrix Inequality Constraint. (17th February 2018) - Ke, Yifen; Ma, Changfeng
ABSTRACT: This paper introduces an alternating direction method of multipliers (ADMM) for finding solutions to a class of Sylvester matrix equation AXB  =  E subject to a linear matrix inequality constraint CXD ≥ G . Preliminary convergence properties of ADMM are presented. Numerical experiments are performed to illustrate the feasibility and effectiveness of ADMM. In addition, some numerical comparisons with a recent algorithm are also given.